Randomised comparison of needle aspiration and chest tube drainage in spontaneous pneumothorax. Issue 4 (13th April 2017) - Thelle, A.; Gjerdevik, M.; SueChu, M.; Hagen, O. M.; Bakke, P.
Guidelines on spontaneous pneumothorax are contradictory as to intervention between needle aspiration (NA) and chest tube drainage (CTD). Studies show poor adherence to guidelines. Three Norwegian hospitals included patients with primary (PSP) and secondary (SSP) spontaneous pneumothorax. Patients underwent NA or CTD as the primary intervention. The main outcome was duration of hospital stay. Secondary outcomes were immediate- and 1-week success rates and complications. 127 patients were included, including 48 patients with SSP. 65 patients underwent NA, 63 patients CTD. Median (interquartile range) hospital stay was significantly shorter for NA: 2.4 days (1.2–4.7 days), compared with CTD: 4.6 days (2.3–7.8 days) (p<0.001). The corresponding figures for the SSP subgroup were 2.54 days (1.17–7.79 days) compared with 5.53 days (3.65–9.21 days) (p=0.049) for NA and CTD, respectively. Immediate success rates were 69% for NA compared with 32% for CTD (p<0.001). The positive effect of NA remained significant in sub-analyses for SSP. There was no significant difference in 1-week success rates. Complications occurred only during the CTD-treatment. Our study shows shorter hospital stay and higher immediate success rates for NA compared with CTD. Subgroup analyses also show clear benefits for NA for both PSP and SSP. Needle aspiration as treatment leads to shorter hospital stay in primary and secondary spontaneous pneumothorax http://ow.ly/tmMU309dB8V